The Effect of High-Power and Low-Power Lasers on Symptoms and the Nerve Conduction Study in Patients With Carpal Tunnel Syndrome. A Prospective Randomized Single-Blind Clinical Trial: The Effect of Laser Therapy on Carpal Tunnel Syndrome - Hojjati, Fateme; Afjei, Mohammad Hosein; Ebrahimi Takamjani, Ismail; Rayegani, Seyed Mansour; Sarrafzadeh, Javad; Raeissadat, Seyed Ahmad; Payami, Sara (Journal of Lasers in Medical Sciences, 2020)
Introduction: Carpal tunnel syndrome (CTS) is the most common peripheral nerve entrapment. Various treatments have been suggested for CTS and there is no consensus on their superiority and the order of their use. Laser therapy is a non-invasive treatment method for many musculoskeletal diseases, including CTS. This study aimed to determine and compare the effect of high-power lasers (HPLs) and low-power lasers (LPLs) on pain severity, function, pinch strength, and nerve conduction study findings in patients aged 30-50 years with mild or moderate CTS. Methods: This is a prospective, randomized, single-blind clinical trial. The study population included 45 patients aged 30-50 years who came to the physical medicine and rehabilitation clinic of Shohada-e-Tajrish hospital and mild or moderate CTS was confirmed for them. Patients were randomly assigned to control, LPL therapy, and HPL therapy groups. Pain, function, pinch strength, and nerve conduction study findings were recorded in all groups before, immediately and 12 weeks after the treatment. All data were compared using SPSS version 21. Results: All groups showed improvement regarding pain, function, and pinch strength. Laser therapy showed significantly better results compared to a wrist splint, but no significant difference was seen between high-power and LPL therapy groups. Nerve conduction evaluation findings did not reveal any significant difference. Conclusion: Both the wrist splint and laser therapy can improve the symptoms of carpal tunnel syndrome. HPL therapy showed better results, although not significantly different from LPL therapy.